Q&A - Ask Doubts and Get Answers
Q

Use a suitable identity to get each of the following product. (-a+c)(-a+c)

Q : 1   Use a suitable identity to get each of the following product.

            (viii) (-a+c)(-a+c)

Answers (1)
Views

take (-)ve sign common from both the brackets So, our question become
                                                                                 (a -c) X (a -c) =(a -c)^{2}
We use identity II for this which is 
                                                      (a-b)^{2} =a^{2} -2ab + b^{2}
In this a = a and b = c
                                             (a-c)^{2} =a^{2} -2ac + c^{2}

Exams
Articles
Questions